2016
DOI: 10.1038/ncomms12927
|View full text |Cite|
|
Sign up to set email alerts
|

Interplay between evanescence and disorder in deep subwavelength photonic structures

Abstract: Deep subwavelength features are expected to have minimal impact on wave transport. Here we show that in contrast to this common understanding, disorder can have a dramatic effect in a one-dimensional disordered optical system with spatial features a thousand times smaller than the wavelength. We examine a unique regime of Anderson localization where the localization length is shown to scale linearly with the wavelength instead of diverging, because of the role of evanescent waves. In addition, we demonstrate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 46 publications
5
29
0
Order By: Relevance
“…Moreover, in connection with our assumption of TE polarization, once again to facilitate direct comparison with the results from previous related studies [20,24,26,27], we note that enhanced nonlocality generally occurs for the transverse-magnetic polarization as well [20], although its visibility may be less pronounced [21].…”
Section: Some Remarkssupporting
confidence: 79%
See 2 more Smart Citations
“…Moreover, in connection with our assumption of TE polarization, once again to facilitate direct comparison with the results from previous related studies [20,24,26,27], we note that enhanced nonlocality generally occurs for the transverse-magnetic polarization as well [20], although its visibility may be less pronounced [21].…”
Section: Some Remarkssupporting
confidence: 79%
“…Our outcomes constitute a first step toward extending the previous studies on periodic [20][21][22][23][24][25][26] and randomly disordered [27,28] geometries to the intermediate realm of "orderly disorder" and, albeit focused on a specific geometry, provide some generally applicable tools.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Overall, the assumed parameter regime is rather unusual, as the phase-accumulation mechanism is essentially dominated by the discrete jumps (Fresnel-type reflection/transmission) at the layer interfaces rather than the delay acquired via propagation through the (deeply subwavelength) layers. In previous studies on periodic and aperiodic structures [8,14,16,17,20], it was shown that such mechanism can lead to the buildup of boundary effects that can substantially enhance the (otherwise negligible) nonlocal effects, thereby yielding strong departures of the optical response from the EMT predictions. These effects tend to be particularly enhanced nearby the critical angle defining the total-internal-reflection condition for the effective medium, θ c = arcsin ε /ε e = 60 o .…”
Section: Generalitiesmentioning
confidence: 99%
“…Interestingly, these phenomena are not limited to periodic arrangements. In particular, anomalous Anderson localization was observed theoretically [16] and experimentally [17] in randomly disordered dielectric multilayers, once again in a deeply subwavelength regime where conventional EMT predicts instead a moderately transmissive response. More recently, inspired by the permeating concept of "quasicrystals" [18,19], we have started exploring aperiodically ordered multilayer geometries, lying in between perfect periodicity and random disorder.…”
Section: Introductionmentioning
confidence: 99%